2021
DOI: 10.7861/clinmed.2020-0896
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic dysfunction in ‘long COVID’: rationale, physiology and management strategies

Abstract: The SARS-CoV-2 (COVID-19) pandemic has caused unprecedented morbidity, mortality and global disruption. Following the initial surge of infections, focus shifted to managing the longer-term sequelae of illness in survivors. 'Post-acute COVID' (known colloquially as 'long COVID') is emerging as a prevalent syndrome. It encompasses a plethora of debilitating symptoms (including breathlessness, chest pain, palpitations and orthostatic intolerance) which can last for weeks or more following mild illness. We describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
482
1
49

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 545 publications
(608 citation statements)
references
References 28 publications
17
482
1
49
Order By: Relevance
“…It has been suggested that SARS-COV-2 infection may impair cognitive function that would lead to brain fog via selective targeting of the mitochondria of the neurons (96). Dani et al described long COVID symptoms, such as, tachycardia, palpitation, orthostatic intolerance, breathlessness, and chest pain as the consequences of autonomic nervous system instability caused by deconditioning hypovolemia or immune-or virus-mediated autonomic nervous system destruction (102). In a case report of a COVID-19 patient with anti-microbial resistant Pseudomonas Aeruginosa infection, it was documented that 6 weeks after clearing of the viral infection, a significant number of activated T-cells and T-cells-specific for unrelated antigens were present, suggesting "a significant amount of by stander activation" which might contribute to recurring anti-bacterial-resistant infections (152).…”
Section: ) Pathophysiologymentioning
confidence: 99%
“…It has been suggested that SARS-COV-2 infection may impair cognitive function that would lead to brain fog via selective targeting of the mitochondria of the neurons (96). Dani et al described long COVID symptoms, such as, tachycardia, palpitation, orthostatic intolerance, breathlessness, and chest pain as the consequences of autonomic nervous system instability caused by deconditioning hypovolemia or immune-or virus-mediated autonomic nervous system destruction (102). In a case report of a COVID-19 patient with anti-microbial resistant Pseudomonas Aeruginosa infection, it was documented that 6 weeks after clearing of the viral infection, a significant number of activated T-cells and T-cells-specific for unrelated antigens were present, suggesting "a significant amount of by stander activation" which might contribute to recurring anti-bacterial-resistant infections (152).…”
Section: ) Pathophysiologymentioning
confidence: 99%
“…Most studies refer to their patient recruitment in terms of recovery (e.g., "COVID-19 survivors" 56 or "discharged COVID-19 patients" 57 ) or clinical course (e.g., "medium-and long-term consequences" 58 or "delayed return to usual health" 59 ). A number of studies did refer to their participant groups using terms like "Long COVID", 13,[60][61][62][63][64][65][66][67][68] "post-acute COVID-19", 69,70 "post-COVID syndrome", 71 or "post-acute COVID-19 syndrome", 72 but these terms were not standardized among studies. A few studies 46,60 acknowledged the proposed distinction at 12 weeks post-infection between post-acute COVID-19 and chronic COVID-19, 37 but otherwise the definitions used typically did not refer to any proposed operationalizations of Long COVID.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A number of studies did refer to their participant groups using terms like "Long COVID", 13,[60][61][62][63][64][65][66][67][68] "post-acute COVID-19", 69,70 "post-COVID syndrome", 71 or "post-acute COVID-19 syndrome", 72 but these terms were not standardized among studies. A few studies 46,60 acknowledged the proposed distinction at 12 weeks post-infection between post-acute COVID-19 and chronic COVID-19, 37 but otherwise the definitions used typically did not refer to any proposed operationalizations of Long COVID. Therefore, while operational definitions of the constituent components of Long COVID have been proposed, 37,42,44 reviewing the Long COVID literature revealed that they are rarely used when describing cases or identifying study cohorts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While substantial research has sought to characterize the disease natural history and the acute management of COVID-19, comparatively fewer studies have focused on the post-acute sequelae of SARS-CoV-2 infection (PASC) [1][2][3][4][5][6] . Much of the publicly available data on PASC come from case reports and single-institution prospective cohort studies [7][8][9][10][11][12][13] . Patient reported symptom data have shown that prolonged fatigue, headache, dyspnea and anosmia are PASC symptoms 14 .…”
Section: Introductionmentioning
confidence: 99%